The Economic Journal - Royal Economic Society (England) (St. Andrews Royal Economic Society, 1990)
The ​journal provides a platform for high quality and imaginative economic research, it containis high quality refereed articles offering some of the best new work in theoretical, applied and empirical research from across all fields of economics.
Full text articles are available from JSTOR: https://www.jstor.org/journal/economicj
Keywords: Economics; ECONOMICS; ECONOMIC RESEARCH; PERIODICALS